Billing Practices in Buy Now Pay Later Services and Their Impact on Consumer Complaints - Arsendi Arsendi; Rina Djunita Pasaribu (Eastasouth Institute, 2026)
The development of Buy Now Pay Later (BNPL) services in Indonesia has shown significant growth in tandem with the increasing adoption of digital financing by the public. However, this growth has also been accompanied by a rise in consumer complaints related to the operational practices of financing companies. This study aims to analyze the role of collection mechanisms as the primary factor triggering consumer complaints regarding BNPL services in Indonesia. The research method employed is a qualitative approach using a case study design. Data were collected through in-depth interviews with twelve informants comprising representatives from financing companies, regulators, and consumers using BNPL services, supplemented by secondary data from industry reports. The results indicate that collection mechanisms are the dominant factor driving consumer complaints, particularly regarding high collection intensity, the use of inappropriate language, and the involvement of third parties that tend to be aggressive. Additionally, a lack of transparency in information and flexibility in addressing consumers’ financial conditions further reinforces perceptions of unfairness in the service. These findings indicate that collection mechanisms serve not only as risk control tools but also as primary determinants in shaping consumer experience and satisfaction. This study implies that financing companies need to improve their collection practices to be more consumer-protection oriented, and encourages regulators to establish clearer operational standards for BNPL services.